Persepsi Petani Terhadap Asuransi Pertanian Sebagai Upaya Meminimalkan Risiko Gagal Panen di Lahan Sawah (Studi Kasus Petani Padi di Kabupaten OKI Sumatera Selatan) - Nurilla Elysa Putri; Muhammad Yamin; Eries Anggraini; Ary Hayati (Jurnal Ekonomi Pertanian dan Agribisnis, 2019)
Agricultural insurance is one solution for farmers to minimize the risk of crop failure. The condition of climate change, especially flooding that occurs in paddy fields, of course requires an effort to minimize the risk of crop failure for farmers, one of the efforts that have been made is to provide agricultural insurance for farmers. In Ogan Komering Ilir (OKI) Regency this agricultural insurance program has been implemented. Therefore research or study is needed on farmers 'perceptions of agricultural insurance as an effort to minimize the risk of crop failure, so the purpose of this study is to measure farmers' perceptions of agricultural insurance as an effort to minimize the risk of crop failure in rice fields.  Identify what factors support and hinder the implementation of insurance and formulate recommendations for developing agricultural insurance that can be done.  Hasil dari penelitian ini menujukkan bahwa Persepsi Petani terhadap asuransi Pertanian secara umum sangat baik. Indikator yang masih perlu diperbaiki adalah sosialisasi asuransi pertanian yang baru dilakukan satu kali serta perbaikan pada jumlah klaim asuransi yang diajukan petani baik dari lamanya waktu pembayaran maupun dalam jumlah klaim yang dibayarkan. Rekomendasi pengembangan program yang diprioritaskan agar asuransi pertanian dapat berkelanjutan adalah kegiatan sosialisasi secara berkala dari pihak perusahaan penyedian asuransi pertanian, pemilahan tingkat premi dan klaim berdasarkan tipologi lahan, peninjauan langsung oleh pihak asuransi saat ada klaim yang diajukan petani sehingga lebih objektif.